Audit Tata Kelola Teknologi Informasi dalam Mendukung Penerapan Good Corporate Governance (Studi Kasus PT XYZ) - Simatupang, Agustin; Adrianto, Henricus Judi (Diponegoro University, 2024)
The development of Information Technology (IT) is rapidly growing and has increasing risks. Based on the Decision of the Ministry of State-Owned Enterprises S-122-MBU-DSI-05-2021 regarding the implementation guidelines for the assessment of IT Maturity Levels, companies are required to carry out an independent assessment of the maturity level of information technology. This research aims to assess the governance of IT risk management using the COBIT 2019 framework. The research method was carried out using descriptive qualitative methods using the COBIT 2019 framework and literature review, as well as through interviews, observations, questionnaires and review of company documents. The assessment results showed an average maturity level of 3.00 (Established) for 2 COBIT 2019 processes which were considered relevant to Information Technology Risk Management. On average, the 2019 COBIT processes have been implemented at PT XYZ is already running well with the IT risk management maturity level at level 3 and initiatives are still needed to reach maturity level 4 or better. Maturity level 3 means the process has been managed and achieved its goals in a more organized manner using organizational assets and resources. The process has been well defined with policies and standard operating procedures for the process and is carried out in accordance with good risk management and supports the Good Corporate Governance. In the process of increasing the maturity level of information technology risk management to higher level, there are 7 (seven) main recommendations to be implemented so that the information technology risk management process can improve and the implementation of recommendations from the assessment results will be prioritized in the implementation roadmap IT according to Company needs and targets.